INCLUSIVE EDUCATION IN THE PROCESS OF CONSTRUCTION OF A SOCIAL STATE - Shafiev, U.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The article analyzes an inclusive society in the context of building a welfare state, discusses the current state of inclusive education in Azerbaijan, current problems in this area, and also describes the problems it faces. and the legal issues of inclusive education are also one of the issues discussed in this article. The task is solved based on the analysis of world experience by the comparative method. Despite the fact that Azerbaijan has a number of important problems in the field of inclusive education, our country has taken the necessary steps in this direction: it is well known that inclusiveness covers not only the education sector, but also the entire life of society and the state. Research is under way to analyze the relationship between economic performance and the level of inclusive development in the world. In some cases, the concepts of inclusion and integration are mistakenly used as equivalents in the field of education. Of course, this is not a professional approach: integration is the process of adaptation of students to the characteristics of the school, while in the process of inclusion, the school creates a curriculum to support students in accordance with their educational needs.